Cytokine profile in children with newly diagnosed tuberculosis - O. M. Raznatovska; Yu. V. Mironchuk (Zaporožskij Medicinskij Žurnal)
Nowadays, the most important task of children's phthisiology is to increase the effectiveness of children with tuberculosis treatment, and in the first priority should be given to the first time diagnosed tuberculosis (FTDTB). Examination of the immune system state by cytokine profile in blood serum studying is paid to sufficient attention, as cytokines are the system which regulates the entire complex of organism protective reactions, and immunological dysregulation is the cause of pathological process increasing. There few data of the cytokine profile state studying in children with FTDTB inUkraine in the available literature and various combinations of cytokines comprehensively with other immunological parameters are studied. According to our studies of the blood serum cytokine profile state in adult patients with tuberculosis, the reliable indices of immune system changes are interleukin (IL)-2, IL-6, IL-4 and IL-10.